Key issues of patient safety during anticancer drug treatment in a day hospital and outpatient setting - A. A. Fedenko; A. A. Kolomeytseva; V. O. Artemova (Онкогематология)
Background. In the context of the ongoing COVID-19 pandemic, the vector of healthcare development is aimed at minimizing contacts among citizens, which is especially important for cancer patients, given the immunosuppression caused by cytostatics.The objective of the review is to present the development prospects of hospital-substituting technologies for drug antitumor treatment. Two main components are considered that allow effective and safe infusion of anticancer drugs in a day hospital: central venous access devices and infusion pumps, various types of these devices, their safety and experience of use today are described.Materials and methods. We searched for available literature published in PubMed, Medline, eLIBRARY, Cochrane Library, CyberLeninka, Global.health, etc. 42 sources were found and analyzed, published from 2002 to 2021.Results. Outpatient anticancer drug treatment is a real alternative to hospital stay, based on many years of world experience. The qualifications level of medical personnel involved in the treatment process should allow early monitoring of various adverse events development. With the ongoing COVID-19 pandemic, it is important to ensure the continuity of the treatment process while minimizing risks to the patient.Conclusion. With a careful approach and adequate infrastructure availability, drug treatment in a day hospital can reduce the burden on round-the-clock stay hospital and positively affect the patients’ quality of life and their compliance with treatment.